Understanding Incidence and Complexity of Obesity and Overweight in Adolescents - Azzini, Vitor Ohana Marques; Lopes, Cristianne Confessor Castilho; Beker , Natascha Szumsztajn; Lopes, Eduardo Barbosa; Lopes, Lucas Castilho; Lopes, Maria Eduarda Castilho; Filho, Mushue Dayan Hampel Vieira; Pitanga, Fábio Herget (Recent Updates in Disease and Health Research Vol. 8, 2024)
Introduction: During recent decades, an alarming increase in the proportion of young people experiencing these conditions has been observed, raising serious concerns about the consequences for the health and well-being of this growing population. The adverse effects of obesity and overweight in adolescence are vast and cover a wide range of physical and mental health problems. Overweight adolescents are at increased risk of developing chronic conditions such as type 2 diabetes, hypertension, cardiovascular disease and musculoskeletal disorders, as well as facing psychosocial challenges such as stigma, low self-esteem and depression. Effective prevention and management of obesity and overweight during adolescence are crucial to reduce the negative impact on individual and collective health, as well as to reduce the social and economic costs associated with these conditions Objective: to contribute to a better understanding of the complexity of obesity and overweight in adolescents, as well as to help in the development of effective and comprehensive approaches to preventing and controlling these conditions, aiming to promote the health and well-being of adolescents. Methods: This study constitutes a systematic review, classified as exploratory and descriptive. The preparation of the research was a bibliographical search in electronic databases on methods associated with RSL (Systematic Literature Review) and the applications of SMARTER (Simple Multi-Attribute Rating Technique using Exploiting Rankings). Results: A comprehensive systematic search of the literature yielded 4125 articles referring to the incidence of obesity and overweight in adolescents, of which 22 articles were eligible to be included in this systematic review. Early childhood adversity, whether emotional or physical, is linked to long-term negative effects on physical and mental health. Chronic stress resulting from these adversities can affect growth and well-being throughout life. The need for comprehensive educational programs on nutrition, involving schools, parents and health professionals, is highlighted in light of inadequate eating habits and decreased physical activity among adolescents. Conclusion: The incidence of obesity and overweight in adolescents represents a significant public health challenge that requires urgent attention and coordinated action at multiple levels. By prioritizing nutrition education, promoting regular physical activity and access to healthy foods, we can not only reduce the incidence of obesity and overweight among adolescents but also improve their quality of life and overall well-being.